Metaphor and Metonymy across Time and Cultures Perspectives on the Sociohistorical Linguistics of Figurative Language - Díaz-Vera, Javier E.; Díaz-Vera, Javier E. (Cognitive Linguistics Research [CLR], 2015)
This volume offers new insights into figurative language and its pervasive role as a factor of linguistic change. The case studies included in this book explore some of the different ways new metaphoric and metonymic expressions emerge and spread among speech communities, and how these changes can be related to the need to encode ongoing social and cultural processes in the language. They cover a wide series of languages and historical stages.